2021
DOI: 10.1038/s41598-021-90494-y
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the metabolic profile of Mytilus edulis reveals molecular signatures linked to gonadal development, sex and environmental site

Abstract: The monitoring of anthropogenic chemicals in the aquatic environment including their potential effects on aquatic organisms, is important for protecting life under water, a key sustainable development goal. In parallel with monitoring the concentrations of chemicals of concern, sentinel species are often used to investigate the biological effects of contaminants. Among these, bivalve molluscs such as mussels are filter-feeding and sessile, hence an excellent model system for measuring localized pollution. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 74 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…GABA is involved in reproduction, notably steroidogenesis (Maguire et al, 2005) and spermatogenesis in scallops (Watanabe et al, 2014;Nagasawa et al, 2015). In Mytilus edulis, analyses along seasons showed that GABA was linked to the gonadal development (Kronberg et al, 2021). Similarly, the co-exposure might cause reprotoxicity in D. polymorpha: 5 µg L -1 CBZ 15 weeks delayed spermatogenesis (Magniez et al, 2018).…”
Section: Specific Molecular Toxicity Pathwaysmentioning
confidence: 99%
“…GABA is involved in reproduction, notably steroidogenesis (Maguire et al, 2005) and spermatogenesis in scallops (Watanabe et al, 2014;Nagasawa et al, 2015). In Mytilus edulis, analyses along seasons showed that GABA was linked to the gonadal development (Kronberg et al, 2021). Similarly, the co-exposure might cause reprotoxicity in D. polymorpha: 5 µg L -1 CBZ 15 weeks delayed spermatogenesis (Magniez et al, 2018).…”
Section: Specific Molecular Toxicity Pathwaysmentioning
confidence: 99%